Application of Value Clarification Technique (Vct) Models in Improving Learning Outcomes in Dangerous Goods Regulation - Ariyono Setiawan; Luthfiyah Nurlaela; Meini Sondang; Eppy Yundra (Journal of Vocational Education Studies, 2020)
Learning in school or in every educational institution has an important role as a media liaison between knowledge and students or students. There are many learning methods or models used in education. Of the many methods or modes, there is one of them is a clarification value technology (VCT) model. The teaching method is a knowledge of teaching methods used by a teacher or instructor. Another understanding is the presentation technique mastered by the teacher to teach or present learning materials to students in class both individually and in groups. the learning method by clarifying the value of the value clarification technique is teaching to shape students in finding and determining a value that is considered good in dealing with a problem through the process of analyzing existing values and embedded in students. Meanwhile, learning outcomes are abilities students have after they have a learning experience. The purpose of this study is to determine the level of learning outcomes of a particular institution. In this study the object of research from an educational institution that is competent in the field of flight is used. The institution is Surabaya Aviation Polytechnic. The subject of learning taken was Regulation of Dangerous Goods at Surabaya Aviation Polytechnic. In addition, this study was also conducted to determine differences in learning outcomes of cadets in the Lessons on Dangerous Goods Regulations in Surabaya Aviation using the Value Clarification Technique (VCT) method. This type of research is Classroom Action Research (CAR). The research carried out is included in the design of one group pretest and possttest research. the research design that contained pretest before being given treatment and posttest after being treated. This research was conducted at Surabaya Aviation Polytechnic. The data analysis technique used is the different test. Based on data management and analysis results, it can be concluded that the application of learning of Value Clarification Techniques can improve the learning outcomes of cadets. This is evidenced by the differences in learning outcomes of Cycle I and Cycle II significantly